Influence of cyclic loading on the nutrition of articular cartilage. - O'Hara, B P (1990)
Articular cartilage is avascular. Nutrients are transported to the cells mainly by diffusion from the synovial fluid. Nutrient transport is also sometimes thought to be assisted by movement of fluid in and out of cartilage in response to cyclic loading of the tissue ('pumping'). The influence of pumping on transport of solutes through cartilage was measured by subjecting plugs of human femoral head cartilage immersed in medium containing radioactive solutes to a simulated walking cycle of 2.8 MPa at 1 Hz. The rate of absorption or desorption of tracers from the cycled plugs was compared with that of unloaded control plugs. For small solutes (urea, NaI) fluid transport did not affect the rate of solute transport significantly. Most major nutrients, such as glucose and oxygen, are small solutes and thus nutrition should not be affected by pumping. The rate of desorption of a large solute (serum albumin), however, was increased by 30-100% in plugs subjected to cyclic loading.